1988
DOI: 10.1002/etc.5620070208
|View full text |Cite
|
Sign up to set email alerts
|

Low chemical concentration and pH as factors limiting the success of inoculation to enhance biodegradation

Abstract: A strain of Pseudomonas that mineralized 1 microgram of p‐nitrophenol (PNP) per milliliter in culture failed to mineralize the compound in nonsterile or sterile lake water. The bacterium did not act on PNP at the pH of the lake water (pH 8.0) or in culture medium at the same pH, although it did mineralize PNP when added to sterile lake water samples adjusted to pH 7.0. A second strain of Pseudomonas that grew and mineralized 1 μg PNP/ml in culture at pH 8.0 and in sterile lake water at pH 7.0 neither mineraliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…Each value is the mean of three replicates ± the standard deviation Table 1 The dissipation kinetic parameters for TBZ dissipation in the soil samples bioaugmented with 5, 50 and 50 mg kg The dissipation data were fitted to the single first order kinetics model and the biphasic model hockey stick and model best fitted to data is shown for each treatment Biodegradation benzyl moiety, possibly as catechol, which was effectively mineralized by the bacterial consortium as demonstrated in the present study. Previous studies have shown that lab-scale liquid culture experiments could be useful to define the range of conditions in which pesticide-degrading bacteria will be active in environmental matrices (Chatterjee et al 1982;Zaidi et al 1988). By doing so, we showed that our consortium was able to effectively degrade TBZ in a range of pH between 4.5 and 7.5, while its degradation capacity was completely halted at highly alkaline conditions (pH 9.0).…”
Section: Discussionmentioning
confidence: 58%
“…Each value is the mean of three replicates ± the standard deviation Table 1 The dissipation kinetic parameters for TBZ dissipation in the soil samples bioaugmented with 5, 50 and 50 mg kg The dissipation data were fitted to the single first order kinetics model and the biphasic model hockey stick and model best fitted to data is shown for each treatment Biodegradation benzyl moiety, possibly as catechol, which was effectively mineralized by the bacterial consortium as demonstrated in the present study. Previous studies have shown that lab-scale liquid culture experiments could be useful to define the range of conditions in which pesticide-degrading bacteria will be active in environmental matrices (Chatterjee et al 1982;Zaidi et al 1988). By doing so, we showed that our consortium was able to effectively degrade TBZ in a range of pH between 4.5 and 7.5, while its degradation capacity was completely halted at highly alkaline conditions (pH 9.0).…”
Section: Discussionmentioning
confidence: 58%
“…First, the temperature was higher than typical in Denmark, which most likely leads to higher biodegradation rates than would occur in nature. Second, the concentration of the antibiotics was higher than expected in the environment, which, as discussed by several authors (Nyholm and Ingerslev, 1997;Zaidi et al, 1988), may lead to arti"cially large amounts of degraders in the test systems and hence to overestimation of biodegradation rates. The third major di!erence from the natural situation was the large amount of water in the test systems, which was used to enable the concentration of the test compounds to be followed using HPLC analysis.…”
Section: Biodegradability Of Three Antibiotics In Soil}manure Slurriesmentioning
confidence: 93%
“…strain Z-4 (17). This is a mutant of a strain originally isolated from Cayuga Lake water, Ithaca, NY, U.S.A., and is resistant to 10 dig of kasugamycin, 100, tg of streptomycin, and 25 ug of spectinomycin per milliliter (Zaidi et al, 1988). The population of this bacterium in water samples was determined by the drop plate method (7) on 0.3% Trypticase soy agar containing the three antibiotics at the indicated concentrations.…”
Section: Methodsmentioning
confidence: 99%